Called for Life: Finding Meaning in Retirement - Clayton, Paul C. (Rowman & Littlefield Publishers, 2008)
Called for Life reflects on our calling to serve God and neighbor in the context of retirement. People facing retirement ask a variety of questions, each framed by a different perspective. "Will I ever be interested in retiring?" some baby boomers ask. "Who am I now?" newly retired clergy ask. "What, if anything, is God calling me to do and be after retirement?" all inquire. This book is built on the assumption that most people don't want to spend the last third of their lives doing nothing. What they want is a life that is worth living, an occupation that will help others, and a retirement in which they can continue to exercise their calling. Clayton uses examples from his own experience and from others, laity and clergy, to explore retirement and the three components of our calling: our identity, our gifts, and our occupation. He also examines the role of community in our calling and retirement, the challenges of the transition into retirement, options for meaningful activity, the importance of identifying our purpose, doing and being in retirement, and the final call to death. Readers will be encouraged to see retirement as an opportunity to do what they have always wanted to do and to become the kind of person they have wanted to be.